Thermal decomposition and combustion of interior design materials; Thermochimica Acta; Vol. 738 - Dorokhov V. V. Vadim Valerjevich; Kuznetsov G. V. Geny Vladimirovich; Kropotova S. S. Svetlana Sergeevna; Sviridenko A. S. Aleksandr Sergeevich; Strizhak P. A. Pavel Alexandrovich (2024, 2024)
Title screen